Pregnancy with Severe Anaemia and Pulmonary Hypertension: A Presentation of Hb E –ß Thalassemia - Habib, Asma; Begum, Sayeda Farida; Akhtaruzzaman, Md; Hossain, Amir (Journal of Bangladesh College of Physicians and Surgeons, 2018)
Abstract not available J Bangladesh Coll Phys Surg 2019; 37(1): 43-45